Perceived role of dietary factors in cancer causation and prevention among university undergraduates (2009)
The impact of cancer on patients, care givers and family could be extremely traumatic, yet predisposition to the disease could be curtailed. Excess fat and calories; inadequate intake of fruits, vegetables, fibre, calcium and other dietary imbalances as well as alcohol, smoking and chronic infections are essential cancer aetiological factors. The purpose of this study was therefore to determine the association between perceived role of dietary factors in cancer causation and prevention. The cross sectional study adopted an exploratory survey technique. It took place in the University of Ibadan, Ibadan, Nigeria. Using multi-stage sampling, 346 undergraduates whose ages ranged between 20 and 30 years participated. They responded to a 51-item questionnaire which tapped information on their demographic characteristics, knowledge of cancer; awareness about dietary factors in cancer causation and prevention, and perception of the role of dietary factors in cancer causation and prevention. Results showed that the respondents' level of awareness of cancer was generally high ((91.9%) with few differences across demographic characteristics. However; the relative importance of the relationship between cancer and diet was underestimated (37.3%), and 12.1% of them completely missed the correct cancer risk factors. Similarly, 92 participants (16.6%) believed that cancer is a supernatural disease that cannot be prevented. One hypothesis was tested using chi square, it revealed that there is a significant association between awareness of cancer and knowledge of the role of dietary factors in cancer causation and prevention (X2=-50.24, df =-2, p=- 0.001). With the relatively high degree of awareness of cancer and acceptance of dietary factors as cancer risk determinants, campaigns which involve skill transfer and removal of barriers to change would enhance cancer preventive behaviour among university undergraduate. It is recommended that improvement in health education through inclusion of contents related to cancer causes, prevention and management, as well as social support programmes including subsidized cancer limiting feeding of undergraduates would be necessary in cancer prevention.